Introduction of the generic sense of ability to adapt scale and validation in a sample of outpatient adults with mental health problems - Franken, Katinka; Schuffelen, Pauline; ten Klooster, Peter; van Doesum, Karin; Westerhof, Gerben; Bohlmeijer, Ernst (Frontiers in Psychology, 2023)
Introduction The ability to adapt is a core aspect of daily human life. Recent models and theories emphasize its essential role for health and well-being. It concerns the perceived ability to readjust and actively deal with the psychosocial consequences of challenging events. While many questionnaires measure competences related to adaptability to specific conditions, a scale that measures a generic sense of the ability to adapt is lacking. The aim of the present study is to introduce the Generic Sense of Ability to Adapt Scale (GSAAS) and to examine its psychometric properties. Methods The article describes two sub-studies. In the first study the items of the GSAAS were generated and field-tested in a cross-sectional non-clinical sample using item analysis, exploratory factor analysis and Rasch analysis. Results This resulted in a 10-item questionnaire measuring a single dimension with good reliability (Cronbach’s α = 0.87). In the second study the 10-item scale was validated using a cross-sectional sample of 496 outpatient adults with mental health problems. Confirmatory factor analysis confirmed the unidimensional structure of the GSAAS and the absence of measurement variance across gender, age and education. Reliability was high (α = 0.89) and moderate to strong correlations between the GSAAS and concurrent validation measures confirmed its convergent validity. Regarding incremental validity, the GSAAS accounted for 7.4% additional explained variance in symptomatic distress above and beyond sense of coherence. Discussion In conclusion, the GSAAS appears to be a reliable and valid instrument to assess people’s generic sense of the ability to adapt. It is a practical and quick tool that can be used to measure a vital aspect of health in research and clinical treatment settings.